2000
DOI: 10.1007/s004410000250
|View full text |Cite
|
Sign up to set email alerts
|

S100-like protein in the goldfish ( Carassius auratus ) kidney

Abstract: The presence and distribution of S100-like protein in the goldfish (Carassius auratus L.) kidney has been studied by the use of immunohistochemical and histochemical methods. Simple immunohistochemistry (peroxidase anti-peroxidase method) was carried out with a polyclonal antibody against a mixture of both S100alpha and S100beta proteins. In order to confirm the cell-type containing S-100-like immunoreactivity, the colocalization of S-100-like protein immunoreactivity with periodic acid-Schiff (PAS) reaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Moreover, the S100 protein IR is colocalized with both neurotrophins showing the same distribution pattern. On the basis of teleost JG cell distribution and their morphological characteristics (Krishnamurty and Bern, 1969), our findings in this report are in agreement with our previous studies (de Girolamo et al, 2000aGirolamo et al, , 2003 that NGF IC and NT-3 IC of goldfish and scorpionfish kidney can be identified as JG cells. These cells correspond to JG cells of higher vertebrates (Elger et al, 1984) that are modified granulated vascular smooth muscle cells, located in the tunica media of preglomerular arterial vessels and are capable of synthesizing renin (Bulger and Trump, 1969;Christensen et al, 1987;Kobayashi and Takei, 1996;Mizogami et al, 1968;Oguri, 1980).…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Moreover, the S100 protein IR is colocalized with both neurotrophins showing the same distribution pattern. On the basis of teleost JG cell distribution and their morphological characteristics (Krishnamurty and Bern, 1969), our findings in this report are in agreement with our previous studies (de Girolamo et al, 2000aGirolamo et al, , 2003 that NGF IC and NT-3 IC of goldfish and scorpionfish kidney can be identified as JG cells. These cells correspond to JG cells of higher vertebrates (Elger et al, 1984) that are modified granulated vascular smooth muscle cells, located in the tunica media of preglomerular arterial vessels and are capable of synthesizing renin (Bulger and Trump, 1969;Christensen et al, 1987;Kobayashi and Takei, 1996;Mizogami et al, 1968;Oguri, 1980).…”
Section: Discussionsupporting
confidence: 95%
“…A IR staining pattern similar to that for NGF and NT-3 was obtained utilizing S100 antibody as juxtaglomerular cell marker (de Girolamo et al, 2000a(de Girolamo et al, , 2003. Moreover, indirect immunofluorescence reactions gave a staining pattern that was superimposable on the immunohistochemical one.…”
Section: Double Immunofluorescence and Confocal Laser Scanning Microsmentioning
confidence: 97%
See 1 more Smart Citation
“…In a previous study, we observed that in the kidney of goldfish, S100-like immunoreactivity was located in JG cells distributed on the arteries but not on the afferent arterioles (de Girolamo et al, 2001). This distribution pattern resembles the one observed in channa kidney and differentiates from the ones of others saltwater fish kidney studied.…”
Section: Discussionmentioning
confidence: 95%
“…S100␣ (S100A1) and S100␤ (S100B) were localized abundantly in mammalian renal cells (Haimoto et al, 1987;Molin et al, 1984), confirming the role of these proteins in the regulation of pH, water, and electrolytes. Recently, we have described for the first time the presence and distribution of S100-like protein in the kidney of a freshwater fish (Carassius auratus) (de Girolamo et al, 2001). S100-like immunoreactivity was detected only in juxtaglomerular cells, and no immunoreactivity was observed in other tracts of the goldfish kidney.…”
Section: Introductionmentioning
confidence: 99%